Implementation of Enforcement of Regional Regulations on Advertising by Batam’s Public Order Agency (Satpol PP) - Haryadi, Nono; Hutasoit, Isfandir; Bhakti, Rizki Tri Anugrah; Kelvin, Edwal (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study examines the implementation of regional regulation enforcement on outdoor advertising (reklame) by the Satpol PP of Batam using a simple quantitative approach. It investigates how’s the implementation factors of —communication, resources, implementers’ disposition and bureaucratic structure/standard operating procedures (SOP)—shape enforcement effectiveness. Data were collected through a 1–5 Likert-scale questionnaire administered to all Satpol PP personnel in Batam (N=82) using a census technique and analyzed in SPSS using descriptive statistics, reliability testing and multiple linear regression. Reliability results indicate that all constructs are internally consistent (Cronbach’s Alpha: communication=0.86; resources=0.88; disposition=0.84; SOP=0.82; effectiveness=0.90). Descriptively, all variables fall within the “high” category, with mean scores of 3.74 (SD=0.56) for communication, 3.45 (SD=0.63) for resources, 3.88 (SD=0.52) for disposition, 3.60 (SD=0.58) for SOP and 3.51 (SD=0.65) for enforcement effectiveness. The regression model is statistically significant (F=34.96; p<0.001) and explains 64.5% of the variance in enforcement effectiveness (R²=0.645). At the partial level, resources (β=0.39; p<0.001), communication (β=0.28; p=0.002) and SOP (β=0.23; p=0.010) have significant positive effects, while disposition is not significant (p=0.201). These findings suggest that enforcement effectiveness is primarily driven by organizational capacity, consistent information flow and procedural clarity rather than individual attitudes alone. The study recommends strengthening the advertising-object database, standardizing escalation procedures within SOPs and enhancing inter-agency coordination to improve enforcement consistency. From a broader policy perspective, these findings indicate that enforcement effectiveness in Batam is shaped less by individual commitment alone than by the city’s ability to maintain a reliable advertising-object database, sustain inter-agency information consistency, and apply SOP-based escalation uniformly across cases. The practical implication of this study therefore lies in strengthening data-driven and procedurally standardized enforcement design, rather than treating effectiveness as a purely operational or attitudinal issue